100 YEARS OF INSULIN: Arresting or curing type 1 diabetes: an elusive goal, but closing the gap. Issue 2 (May 2021) - Martens, Pieter-Jan; Gysemans, Conny; Mathieu, Chantal
Abstract : Type 1 diabetes is one of the most common chronic diseases in children and adolescents, but remains unpreventable and incurable. The discovery of insulin, already 100 years ago, embodied a lifesaver for people with type 1 diabetes as it allowed the replacement of all functions of the beta cell. Nevertheless, despite all technological advances, the majority of type 1 diabetic patients fail to reach the recommended target HbA1c levels. The disease-associated complications remain the true burden of affected individuals and necessitate the search for disease prevention and reversal. The recognition that type 1 diabetes is a heterogeneous disease with an etiology in which both the innate and adaptive immune system as well as the insulin-producing beta cells intimately interact, has fostered the idea that treatment to specific molecular or cellular characteristics of the patient groups will be needed. Moreover, robust and reliable biomarkers to detect type 1 diabetes in the early (pre-symptomatic) phases are wanted to preserve functional beta cell mass. The pitfalls of past therapeutics along with the perspectives of current therapies can open up the path for future research.